The Influence of Gimkit Game Implementation on Students’ Analytical Skills, Engagement, and Satisfaction Levels: Pengaruh Penerapan Game Gimkit terhadap Kemampuan Analitik, Keterlibatan dan Tingkat Kepuasan Mahasiswa - Dwiga Kurniasari; Shinta Puspitasari; Ridwan Ramadhan; Siska Sukma Ayu; Yosepa Juliana Sihombing; Nurdian Susilowati (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This study aimed to analyze the effect of using Gimkit, an interactive game-based learning platform, on students’ analytical skills, engagement, and learning satisfaction in the Introduction to Accounting course. A quasi-experimental design with a Nonequivalent Control Group was employed, involving 80 undergraduate students divided into an experimental class (using Gimkit) and a control class (conventional methods). Research instruments consisted of a 15-item multiple-choice test to measure analytical skills and Likert-scale questionnaires to assess engagement and satisfaction. The instruments were validated using Pearson’s correlation (r > 0.30) and achieved acceptable reliability (Cronbach’s α > 0.70). The results of independent sample t-tests showed no significant differences in analytical skills (t = 0.26, p > .05, d = 0.06) and engagement (t = 0.02, p > .05, d = 0.01) between groups. However, a significant difference was found in learning satisfaction (t = 4.21, p < .001, d = 0.75), with higher satisfaction reported by students in the Gimkit group. These findings suggest that Gimkit is more effective in enhancing affective aspects, particularly satisfaction, rather than cognitive outcomes in the short term. This study provides one of the first empirical insights into Gimkit implementation in accounting education in Indonesia and highlights the need for further longitudinal research to examine its long-term cognitive effects.